Measuring Of Data Base Performance Using Oracle - Heba Raoof; Firas Mustafa (Al-Rafidain Journal of Computer Sciences and Mathematics, 2014)
Due to the tremendous increase in the manufacturing of computer and producing high speed and performance computers, it was very important to find new methods for distinguishing its efficiency, performance and characteristics. Optimization method can be defined as a process of choosing the most efficient way to execute DML statements such as (select, insert, update and delete). In this research, performance efficiency of two different computers specifications by using Oracle system (9i) has been measured, in addition to distinguishing the performance between these two computers, on different data sizes (1000, 5000, 80000,300000 and 600000 records). (SQL) as tools for any comparison can be achieved  by the statistical performance parameters (Cpu time , Logical block read ,physical block read, physical block write,  Process Global Area memory, Execution time). Update command  effect on the parameters Cpu-time, logic_read, phy_read, Phy_Write was higher than select command specially at record number (600000) for both computers. Also, Values of these parameters increased by increasing data size (number of records). The parameters (PGA memory in use, exe_time)  gave ununiform results by increasing data size. The effect of selection and update commands in computer1 on (Cpu_time, logic_read, phy_read, Phy_Write) parameters values were significantly higher compared to computer2 . While, the values of (PGA memory in use, exe_time) parameters in computer2 for both select and update commands were higher compared with computer1, but it was not significant.